DETERMINAN ANEMIA PADA WANITA USIA SUBUR (15-49 TAHUN) PERNAH HAMIL DI INDONESIA - Attaqy, Fella Cika; Kalsum, Ummi; Syukri, Muhammad (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2022)
ABSTRACT Background: Anemia is still a nutritional problem in Indonesia, especially anemia iron deficiency. It is risk factor that contribution the most to maternal mortality in Indonesia. The aim of this study was to analyze dominant determinan of anemia in women of reproductive age (WRA) ever pregnant in Indonesia. Methods: Research design used secondary data analysis from part of the Basic Health Research (Riset Kesehatan Dasar = Riskesdas) 2018 with cross sectional study design. The population were women of reproductive age in aged 15-49 years, and the samples of WRA ever pregnant carried out biomedical examinations as much at 11.854 samples. The independent variables were age, education, occupation, place of recidence, parity, Chronic Energy Deficiency (CED), consumption blood added tablets, disease history, and the dependent variable was anemia measured <12g/dl. The analysis used complex sample chi quare and multiple logistic regression at 95% confidence interval level. Result: The proportions Anemia in WRA ever pregnant in Indonesia was 24.3%. Determinant anemia of WRA ever pregnant were age (Prevalence Odds Ratio (POR): 1.97; 95% Confidence Interval (CI): 1.25-3.10), education (POR: 0.71; 95% CI: 0.63-0.80), CED (POR: 1.86; 95% CI: 1.54-2.25), consumption blood added tablets (POR: 4.57; 95%CI: 3.21-6.49). The dominant factor of anemia in WRA was consumption blood added tablets after controlling by age, education, and CED. Conclusion: WRA are not compliant in taking blood-added likely to experience of anemia. It is necessary to educate about anemia, and good monitoring for teenegers and WRA taking blood-added tablets. Keywords: Anemia, woman reproductive age, consumption blood added tablets ABSTRAK Latar Belakang: Anemia masih menjadi salah satu masalah kurang gizi di Indonesia terutama anemia defisiensi besi yang merupakan salah satu faktor risiko berkontribusi pada kematian ibu di Indonesia. Tujuan penelitian adalah untuk menganalisis determinan anemia pada wanita usia subur (WUS) pernah hamil di Indonesia. Metode: Penelitian ini adalah penelitian analisis data sekunder, menggunakan sebagian data Riset Kesehatan Dasar (Riskesdas) tahun 2018 dengan desain studi cross sectional. Populasi penelitian adalah WUS berusia 15-49 tahun, sampel adalah WUS pernah hamil yang melakukan pemeriksaan biomedis sebanyak 11.854 orang. Variabel bebas adalah usia, pendidikan, pekerjaan, tempat tinggal, paritas, Kurang Energi Kronis (KEK), kepatuhan konsumsi Tablet Tambah Darah (TTD), dan riwayat penyakit, sedangkan variabel terikat adalah anemia yang diukur bila kadar hemoglobin <12 gr/dl. Analisis menggunakan Complex sample Uji Chi Square dan Regresi Logistik Ganda pada tingkat kepercayaan 95%. Hasil: Proporsi anemia pada WUS pernah hamil di Indonesia 24,3%. Determinan anemia WUS pernah hamil yaitu usia (POR: 1,97; 95%CI: 1,25-3,10), pendidikan (POR: 0,71; 95%CI: 0,63-0,80), KEK (POR: 1,86; 95%CI: 1,54-2,25), Kepatuhan konsumsi TTD (POR: 4,57; 95%CI: 3,21-6,49). Faktor dominan terjadinya anemia adalah kepatuhan konsumsi TTD, setelah dikontrol dengan usia, pendidikan dan KEK. Kesimpulan: WUS yang tidak patuh mengkonsumsi TTD lebih berisiko mengalami anemia. Perlu dilakukan edukasi tentang anemia, peningkatan edukasi dan monitoring konsumsi TTD pada remaja dan WUS. Kata Kunci: Anemia, Wanita Usia Subur, Konsumsi Tablet Tambah Darah